Book Review: Sumit Sarkar, Out-Think: How to Use Game Theory to Outsmart Your Competition. (December 2016) - Tandon, Neelam
Sumit Sarkar, Out-Think: How to Use Game Theory to Outsmart Your Competition . New Delhi: SAGE Publications India Pvt Ltd., 2016, 213 pp. ₹395 (ISBN: 978-93-515-0563-1) (Paperback)